Phenotypic Characterization, Genetic Variability and Correlation Studies among Maize Landraces of Manipur - Devi, H. Nanita; Devi, K. Nandini; Singh, N. Brajendra; Singh, T. Ratan; Jyotsna, N.; Paul, Amitava (International Journal of Bio-resource and Stress Management, 2023)
The study was carried out to characterize and access the genetic parameters and character association for eight morphological traits of forty maize landraces collected from 9 districts of Manipur. The accessions were characterized according to three important phenotypic traits, viz., Kernel Colour, Kernel Shape and Kernel Row Arrangement. There were great variations amongst the accessions with regard to kernel colour and kernel shape. Out of the total accessions different kernel colours were observed viz., yellow (9), variegated (9), white (8), black (6), red (4), purple (2), brown (1) and orange (1). Variations due to kernel shape are leveled (25), rounded (10), indented (2), pointed (1), sharply pointed (1), and shrunken (1). Variation due to kernel row arrangement are regular (23), irregular (7), straight (6) and spiral (4). The analysis of variance revealed highly significant differences for all the traits under study indicating adequate for selection. The high estimates for PCV and GCV were obtained for No. of kernels cob-1, 100 kernel wt. and seed yield 5 sq. m-1 revealing that the landraces have a broad genetic background that will respond positively to selection for improving these traits. The correlation coefficients analysis show that the days to maturity and number of kernels cob-1 had significant and positive correlation with seed yield.